Reducing the digital divide for marginalized households - Guglielmo Barone; Annalisa Loviglio; Denni Tommasi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2025)
Digital skills are increasingly essential for full participation in modern life. Yet many low-income families face a dual digital divide: limited access to technology and limited ability to use it effectively. These gaps can undermine adults' ability to support their children's education, restrict access to public services, and reduce their own employability. Despite growing policy attention, rigorous evidence on how to close these gaps-especially among disadvantaged adults in high-income countries-remains scarce. We evaluate the impact of a comprehensive digital inclusion program in Turin, Italy, targeting 859 low-income families with school-aged children. Participants were randomly assigned to a control group or one of two treatment arms, each combining a free tablet with internet access and digital literacy training of different durations. One year later, treated participants reported large improvements in digital skills and daily technology use. Parents also became more confident in guiding their children's online activities, more engaged in digital parenting, and more likely to access public services digitally. We find no short-run effects on employment or job search behavior, but treated participants expressed greater optimism about future training prospects. Effects are statistically similar across the two training intensities, suggesting that once basic barriers are removed, digital engagement can become self-sustaining. Mediation analysis confirms that digital skills-not just access-are key drivers of these outcomes. Sequential effects are particularly strong in the domains of social inclusion and parenting. The findings underscore the importance of addressing both financial and learning constraints and suggest that bundled interventions can foster inclusive digital participation.
Keywords: I24; J24; O33; C93; 330; Digital divide; Digital literacy; Low-income families; Labor market outcomes; Digital parenting